Report on professional attachment with Civil Aviation Authority of Singapore - Ang, Jansen Chee Yong (2008)
I completed my professional attachment (PA) in the Civil Aviation Authority of Singapore?s (CAAS) Internal Audit (IA) Division. The attachment was supposed to be a 10 weeks experience, however, I spent only 9 weeks in CAAS due to my National Service In-Camp Training which lasted for a week from 25th June 2007 to 30th June 2007. This report shall include a detailed description of my 9 weeks PA experience in CAAS.